2022
DOI: 10.3390/pr10102088
|View full text |Cite
|
Sign up to set email alerts
|

Potential Predictors for Cognitive Decline in Vascular Dementia: A Machine Learning Analysis

Abstract: Vascular dementia (VD) is a cognitive impairment typical of advanced age with vascular etiology. It results from several vascular micro-accidents involving brain vessels carrying less oxygen and nutrients than it needs. This being a degenerative disease, the diagnosis often arrives too late, when the brain tissue is already damaged. Thus, prevention is the best solution to avoid irreversible cognitive impairment in patients with specific risk factors. Using the machine learning (ML) approach, our group evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…It seems that neuroinflammation is not the primary process responsible for MS-related mental disability. However, neurodegeneration is a well-known condition that associates cognitive decline through various incompletely explained mechanisms, as research on Alzheimer's disease and other dementias demonstrated [56,57]. This also applies to MS, as cognitive impairment is more frequent and severe in progressive forms of MS than in RRMS [58].…”
Section: Non-modifiable Risk Factorsmentioning
confidence: 99%
“…It seems that neuroinflammation is not the primary process responsible for MS-related mental disability. However, neurodegeneration is a well-known condition that associates cognitive decline through various incompletely explained mechanisms, as research on Alzheimer's disease and other dementias demonstrated [56,57]. This also applies to MS, as cognitive impairment is more frequent and severe in progressive forms of MS than in RRMS [58].…”
Section: Non-modifiable Risk Factorsmentioning
confidence: 99%
“…In [32], multiple healthy dietary guidelines for improving antimicrobial resistance are given through the output of machine learning models. Literature [33][34][35] and highlighted the strong efect of vitamins on obesity, vascular dementia, and Alzheimer's disease through various machine learning algorithms. Essential conclusions that selective nutritional intake efectively reduces COVID-19 infection and mortality have also been drawn using multiple regression models and classifcation algorithms [36,37].…”
Section: Related Workmentioning
confidence: 99%
“…Aging is the primary risk factor for the development of vascular dementia, followed by common vascular risk factors such as hypertension, diabetes mellitus, smoking, and atrial fibrillation [ 7 , 8 ]. These factors contribute to the progressive deterioration of the cerebral vascular system, involving arteries of assorted sizes, leading to neurodegeneration and cognitive decline [ 9 , 10 , 11 ]. Vascular dementia can result from damage caused by acute ischemic events, such as strokes, or chronic brain injuries due to prolonged reduced blood perfusion [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%